Mesozooplankton abundances at timeseries station Helgoland Roads, in 2021 - Boersma, Maarten; Kirstein, Inga Vanessa; Renz, Jasmin (In: Boersma, Maarten; Greve, Wulf; Renz, Jasmin; Ecker, Ursula; Kirstein, Inga Vanessa (2017): Mesozooplankton abundances at time series station Helgoland Roads since 1974 [dataset publication series]. Alfred Wegener Institute - Biological Institute Helgoland, PANGAEA, https://doi.org/10.1594/PANGAEA.873032, 2024)
Samples to detemine zooplankton abundance were collected as part of the Helgoland Roads long-term data series in 2021. Zooplankton were sampled at the "Kabeltonne" site (54°11.3′N, 7°54.0′E) using an oblique haul with a 150µm hand net (Apstein, Hydrobios, Kiel) and preserved in 4% formaldehyde (buffered with Borax) to allow for storage and later examination. Sampling volume was calculated with a mechanic flowmeter (Hydrobios, Kiel). Samples were counted either as whole or as subsamples depending on the density. However, at least 60 individuals of each key species were counted per subsample to ensure counting of a representative part of the sample. Species were identified to the lowest possible taxonomic level using a stereomicroscope (Leica M205C). If identification to the species level was not possible, the next identifiable taxonomic category was assigned.
Keywords: biological time series; Zooplankton